A SYSTEMATIC REVIEW OF SELF-REGULATED LEARNING AND SELF-EFFICACY: KEY DETERMINANTS OF ACADEMIC SUCCESS IN COLLEGE - Priyatna, Muhamad; Raharjo, Raharjo; Fihris, Fihris; Halim, Siti Afiah (Sekolah Tinggi Agama Islam Al Hidayah, 2026)
This study presents a comprehensive systematic review of the role of Self-Regulated Learning (SRL) and Self-Efficacy as primary determinants of academic success in higher education. Through an analysis of more than 120 empirical studies published over the past three decades (1990-2024), this research identifies consistent patterns indicating a positive and significant relationship between these two psychological constructs and various indicators of academic success, including Grade Point Average (GPA), retention, and metacognitive skills. Key findings indicate that self-efficacy serves as both a direct predictor and a strong mediator of academic success, with an average effect size of 0.38 (moderate to large effect). Meanwhile, SRL contributes not only to short-term academic achievement but also to the development of lifelong learning skills. Moderator analysis reveals that these relationships are influenced by cultural context, academic discipline, and learning modality (face-to-face vs. online). This study contributes theoretically by integrating various SRL models and Bandura's self-efficacy theory into a comprehensive conceptual framework. In practice, the review offers recommendations for developing evidence-based interventions to enhance SRL skills and strengthen students' academic self-belief, particularly in the context of higher education in the digital era